2012
DOI: 10.1016/j.lfs.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-related gene expression in the prostate is modulated by doxazosin treatment

Abstract: Our data suggest that relaxation of smooth muscle cells by alpha-blockers interferes with the mechanical dynamics of the prostatic stroma extracellular matrix components, generating a pro-fibrotic effect probably via the TGF-beta 1 signaling pathway. Long term treatment with doxazosin may also lead to a reduced turnover of extracellular matrix components. Our results add to a better understanding of the molecular mechanisms behind the effects of alpha-blockade on prostatic histoarchitecture and the response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…59 Conversely, other studies have shown that the ventral prostates of adult Wistar rats treated with the α-adrenergic receptor antagonist doxazosin contain increased levels of collagen and collagen fibrils compared with untreated controls. 60 A-adrenergic receptor antagonists are known to target vascular and smooth muscle cells in the lower urinary tract. However, myofibroblasts, like smooth muscle cells, are contractile, 55 and further work is required to determine whether myofibroblasts respond to α-adrenergic receptor antagonists in a similar manner to smooth muscle cells in the lower urinary tract.…”
Section: Therapeutic Targeting Of Fibrosismentioning
confidence: 99%
“…59 Conversely, other studies have shown that the ventral prostates of adult Wistar rats treated with the α-adrenergic receptor antagonist doxazosin contain increased levels of collagen and collagen fibrils compared with untreated controls. 60 A-adrenergic receptor antagonists are known to target vascular and smooth muscle cells in the lower urinary tract. However, myofibroblasts, like smooth muscle cells, are contractile, 55 and further work is required to determine whether myofibroblasts respond to α-adrenergic receptor antagonists in a similar manner to smooth muscle cells in the lower urinary tract.…”
Section: Therapeutic Targeting Of Fibrosismentioning
confidence: 99%
“…Treatment with 5ARIs only reduces glandular tissue whereas the relative abundance of stromal and epithelial cells in BPH nodules is diverse suggesting that this treatment may become less efficient in cases with stromal dominance 12 . Furthermore, both 5ARI and a-B stimulate the TGFβ profibrotic pathway and thus may promote fibrosis 13,14 . In agreement with this, the MTOPS (Medical Therapy of Prostatic Symptoms) study revealed that fibrosis in the transition zone of the prostate is associated with increased risk of clinical progression of LUTS in patients who received combined a-B and 5ARI treatement 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of COL3A1 is frequently correlated with the fibrotic phenotype of the prostate and an active TGF-β1 signaling pathway [ 9 , 10 , 11 ]. Moreover, downregulation of COL3A1, using anti-fibrotic agents, has been correlated with the attenuation of the fibrotic phenotype in different organs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Therefore, COL3A1 could potentially serve as marker for the fibrotic phenotype in the tissues and organs of the pelvis exposed to radiation.…”
Section: Introductionmentioning
confidence: 99%